Goldratt and the theory of constraints. the quantum leap in management. - Techt, Uwe (QuiStainable business solutions.)
Businessmen and managers, consultancy clients, readers of the Goldratt novels, and workshop attendees often ask: What is this Theory of Constraints' How can it benefit me' How is it different from other management theories' Is there something I can read to quickly understand its fundamentals' This book is an answer to these questions. Using engaging language and offering many real-life examples, it provides an overview of the methods and tools of the Theory of Constraints: Drum-Buffer-Rope, Buffer Management, Throughput Accounting, Pull Distribution, Irresistible Offer, Corporate Strategy, and Viable Vision. You will learn how to recognize and use constraints, how to complete projects quickly and reliably, and how to gain a competitive lead and to turn it into profit.